The effect of bariatric-metabolic surgery on selected components of metabolic syndrome and visceral adipose tissue - the pilot study - Horká, Veronika; Bužga, Marek; Macháčková, Jitka; Holéczy, Pavol; Švagera, Zdeněk (Physiological research, 2023)
The aim of this study was to monitor changes in the components of the metabolic syndrome defined by Adult Treatment Panel III and the risk of adipose tissue. The study population consisted of 45 patients (30 women, 15 men) who underwent one bariatric procedure - partial jejuno-ileal derivation (n=17), sleeve resection (n=14) or laparoscopic gastric - plication (n=14). Components of metabolic syndrome such as waist circumference, morning glycemia/antihypertension, TAG, HDL cholesterol and blood pressure (BP)/antihypertension were monitored in probands. In addition, Dual Energy X-Ray Absorciometry measurements were performed. Parameters were monitored over the course of one year. The study shows that it is an effective method of weight reduction for the study population with metabolic effects in the risk components of metabolic syndrome - fasting glycemia, increase in HDL cholesterol and reduction in triacylglycerols in the blood, reduction in waist circumference and BP or direct disappearance of metabolic syndrome. Significantly, of the entire cohort, 68.9 % of the probands studied showed signs of metabolic syndrome when measured before the intervention. At the end of follow-up, only 22.2 % of probands showed metabolic syndrome. It was also found that if the amount of visceral fat was reduced, the overall risk of metabolic syndrome was also reduced. The study demonstrates a significant positive effect of bariatric surgery on parameters of metabolic syndrome. The study also showed a positive effect of reduced visceral fat volume on the components of metabolic syndrome.
Keywords: dospělí; Female; Bariatric Surgery; Adult; ženské pohlaví; Metabolic Syndrome; lidé; Intra-Abdominal Fat; Pilot Projects; pilotní projekty; metabolický syndrom; Male; Cholesterol, HDL; index tělesné hmotnosti; bariatrická chirurgie; HDL-cholesterol; nitrobřišní tuk; mužské pohlaví; tuková tkáň; Adipose Tissue; Body Mass Index; Humans